2021
DOI: 10.3390/vaccines9060585
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Acceptance and Its Influencing Factors: An Online Cross-Sectional Study among International College Students Studying in China

Abstract: Background: With the continuous large-scale development of the COVID-19 vaccine, the acceptance of vaccination and its influencing factors at the individual level have become crucial to stemming the pandemic. This study aims to explore the factors that influence the acceptance of the COVID-19 vaccine among international college students. Methods: The target population constituted international students pursuing various degrees in Jiangsu Province through an online cross-sectional study. A cluster random sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 30 publications
2
43
2
1
Order By: Relevance
“…Among the factors explored, a few findings contrasted with the literature. Whereas it has been reported that either female respondents are less likely to intend to vaccinate [12,15] or there is no association with gender [21,33,34], in our study male participants were more likely to be hesitant. In addition, while in the general population different rates of hesitancy have been found according to the country studied [12], we did not detect any difference in terms of nationality, probably reflecting a mitigation of attitudes due to all our respondents being exposed to the same Italian environment.…”
Section: Discussioncontrasting
confidence: 98%
“…Among the factors explored, a few findings contrasted with the literature. Whereas it has been reported that either female respondents are less likely to intend to vaccinate [12,15] or there is no association with gender [21,33,34], in our study male participants were more likely to be hesitant. In addition, while in the general population different rates of hesitancy have been found according to the country studied [12], we did not detect any difference in terms of nationality, probably reflecting a mitigation of attitudes due to all our respondents being exposed to the same Italian environment.…”
Section: Discussioncontrasting
confidence: 98%
“…Provinces in China, on the other hand, report variable results. In Mainland China, Shanghai and Shenzhen, people expressed high intention to vaccinate(with acceptance rates higher than 80%), while the proportion of affirmative population was considerably lower in Hong Kong [46] , Wuxi [47] and Jiangsu province [48] (34.8%, 51.2% and 36.4%, respectively). It should be noted that the surveys were conducted in different time points, which might have imposed an effect on the final results.…”
Section: Resultsmentioning
confidence: 99%
“…Non-Czech students had a substantially higher level of COVID-19 vaccine acceptance (79.9%) compared to international students in China (36.4%) where the international students were challenged by various barriers for getting vaccinated, including the potential side effects, vaccine availability, interrupting their routine activities, and insufficient knowledge about vaccine safety [ 56 ]. In Qatar, citizens were 1.68 times ( CI 95%: 1.30–2.16; Sig.…”
Section: Discussionmentioning
confidence: 99%